Cover Feature: Responsive Fluorophore Aggregation Provides Spectral Contrast for Fluorescence Lifetime Imaging (ChemBioChem 15/2020). (16th July 2020) - Schleyer, Kelton A.; Datko, Benjamin D.; Burnside, Brandon; Cui, Chao; Ma, Xiaowei; Grey, John K.; Cui, Lina
Abstract : Fluorophores are greatly influenced by their environment . In their full paper, L. Cui et al. show that triggering the aggregation of a self‐condensing scaffold labeled with a fluorophore induces changes in the emission spectrum, polarization, and lifetime. The aggregates exhibited a shorter lifetime detectable in cells by fluorescence lifetime imaging microscopy, thus suggesting that triggered aggregation strategies can be used in the probes for various biological events through lifetime imaging.